Upaya Hukum Terhadap Wanprestasi Dalam Perjanjian Kerja Sama Bisnis Pada Perusahaan Pertambangan - Suryanegara, Ip. Deka; Siregar, Hamdan Azhar (Legalita, 2025)
Business cooperation agreements are important instruments in the business world, including in the mining sector, which has high investment characteristics and significant risks. However, in practice, there are often breaches of contract by one party that can harm the other party, both materially and operationally. This thesis discusses the common forms of breaches that occur in business cooperation agreements in mining companies, the factors causing them, and the legal remedies that can be pursued by the aggrieved party. This research uses a normative juridical method with a legislative approach and case studies of several court decisions related to disputes in the mining sector. The research findings show that breaches often occur in the form of delays in fulfilling obligations, violations of technical clauses, and denial of the distribution of business results. Legal efforts that can be pursued include non-litigation efforts such as mediation and arbitration, as well as litigation efforts through the courts. In addition, the importance of including dispute resolution clauses and penalties in agreements becomes a crucial factor in providing legal certainty and protection for the parties. This thesis concludes that careful and comprehensive drafting of cooperation agreements, as well as the selection of appropriate dispute resolution mechanisms, are preventive and solution-oriented steps in dealing with the potential for default in the mining sector.